Microbiological and Chemical Evaluation of Traditional Fermented Skimmed Milk (nono) in Kano State Nigeria - Nassarawa, Sanusi Shamsudeen; Sulaiman, Salamatu Ahmad (International Journal of Food Sciences, 2020)
Purpose: Culturally, consumption of local fermented skimmed milk (nono) is common in Northern Nigeria and many other parts of Africa. However, this is, associated with foodborne related diseases resulting from poor hygienic practices. Methodology: Purposive sampling was used to collect a total of 12 different fermented products from Kano metropolis, Kano State, Nigeria. Findings: The results obtained showed ranges of different parameters as Ph (4.890±0.01414 to4.450±0.07071), titratable acid value (0.315±0.06364 to0.270±0.0000), moisture content (92.090±10.5640 to 80.730±3.7760) and total solid (19.270±3.7760 to 7.910±10.5604). The total bacterial count ranged from (8.766 ±0.3512 Ã— 103 CFU/ml(log104.94) to 1.150 ±0.0700 Ã— 103 CFU/ml (log10 4.06), with fungal count of 2.400 ±0.2646 Ã— 103 CFU/ml (log10 4.38) to 0.733 ±0.1528 Ã— 103 CFU/ml(log10 3.87), coliform count of 14 to <3 (MPN/ml) and Staphylococcal count between the ranged of 8.567 ±0.7095 Ã— 103 CFU/ml (log10 4.92) to 2.867 ±0.9504 Ã— 103 CFU/ml (log10 3.46). The bacteria isolated were Staphylococcus spp, Bacillus spp, Micrococcus spp, Streptococcus, and E. coli, Moreover, the fungal isolates from the samples included Aspergillus niger, Aspergillus flavus, Mucor and Rhizopus stolonifera. The fermented skimmed milk consumed in the study area was found to be of low quality. Thus, awareness should be strengthened on hygienic methods of production, handling, and selling to the consumers. Unique contribution to theory, practice and policy: This study was conducted to assess the microbial quality and chemical parameters that determined the safety of the products